Forensics Investigation on Image Files using Quantization Value - Sabam Parjuangan; Muhammad Hafif; Suhardi Suhardi (Proceeding International Conference on Information Technology and Business, 2020)
Image files were one of the evidences as a result of the forensic investigations on cybercrimes. The process of acquiring the evidence must have a high accuracy. The image files were obtained from social media that had incomplete metadata. This article outlined an in-depth approach for forensic investigation on image files. The method of this forensic examination conducted to the image files was through the investigative action procedures so that the incomplete metadata can still be analyzed. The data analysis technique used in this study was JPEG Analysis, ELA, and Noise methods. The result of this study was that the characteristics of the image files were able to be identified from social media through editting, and originating processes. The forensic measures described in this study were also able to prove the image file modifications.Keywords: Image Forensics, Cybercrimes, Quantization